Pre-Service EFL Teachers’ Perceptions of Online Instructional Tools - Bayram, İlknur; Baturay, Meltem Huri (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2022)
This study carried out with the participation of 68 pre-service EFL teachers (PET) attending Turkish universities aims to investigate PETs’ perceptions as to the use of online instructional tools (OIT). This is a mixed-methods study; both quantitative and qualitative data have been collected. Data was gathered in the academic year of 2018-2019 through an online questionnaire developed by the researchers. The survey was comprised of three sections; (1) demographics, (2) the frequency of teacher educators’(TE) and PETs use of OITs in an English language teacher education program, (3) PETs’ intention of using OITs upon graduation. Two open-ended questions were also asked to find out what might motivate or discourage PETs from using OITs when they become teachers. Results indicate that TEs always use and PETs mostly plan to use videos and presentation tools when they start serving as teachers. However, TEs do not make use of MOOCs, online ELT courses, and blogs as much as expected. Similarly, PETs do not plan to integrate them into their teaching. The reasons underlying their choices are presented in the study.